The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11669-008-9247-6
|View full text |Cite
|
Sign up to set email alerts
|

Details on the Formation of Ti2Cu3 in the Ag-Cu-Ti System in the Temperature Range 790 to 860 °C

Abstract: Silver-copper-titanium (Ag-Cu-Ti) ternary alloys are often used as active braze alloys for joining ceramics to metals at temperatures ranging from 780°C (the melting point of the Ag-Cu eutectic) up to 900°C. When Ti/Ag-Cu joints are brazed at low temperature (near 800°C), the intermetallic compound Ti 2 Cu 3 (tetragonal, P4/nmm, a = 0.313 nm, c = 1.395 nm) is systematically missing from the interface reaction layer sequence. An experimental investigation based on isothermal diffusion experiments in the Ag-Cu-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 8 publications
3
14
1
Order By: Relevance
“…After corrections for atomic number, absorption and fluorescence, the atomic contents of Ag, Cu and Ti were obtained with an accuracy better than ± 0.5 at%. It had been previously verified by X-ray powder diffraction [7] that the crystalline phases for which each interface reaction layer or crystal analysed were effectively obtained under the same heat-treatment conditions.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…After corrections for atomic number, absorption and fluorescence, the atomic contents of Ag, Cu and Ti were obtained with an accuracy better than ± 0.5 at%. It had been previously verified by X-ray powder diffraction [7] that the crystalline phases for which each interface reaction layer or crystal analysed were effectively obtained under the same heat-treatment conditions.…”
Section: Methodsmentioning
confidence: 84%
“…For these reasons, it was decided to further investigate the chemical interaction between titanium and the eutectic Ag-Cu alloy at temperatures down to 780 °C, the temperature of the eutectic transformation. In the first approach at investigating the kinetics of compound formation in the Ag-Cu-Ti system, cold-pressed mixtures of Ag, Cu and Ti powders were heated at 700-860 °C and characterized [7]. In the present work, additional experiments have been carried out at 780-800 °C on Ti/Ag-Cu semi infinite couples and Ti/Ag-Cu/Ti sandwiches in order to determine the extent and constitution of the interface reaction zone formed between solid Ti and liquid Ag-Cu eutectic alloy.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13,20,[34][35][36] However, contrary to the present observations, Shiue et al [19] and Shafiei et al [20] reported the formation of the Cu 4 Ti phase in the BZ, whereas they did not report the formation of Cu 3 Ti 2 phase which formed conspicuously in the present study. Andrieux et al [40] in an experimental investigation on the phase stability study on the Cu-Ti system showed that the Cu 3 Ti 2 phase is stable and can form by solid state reaction in a temperature range of 1063 K to 1133 K (790 C to 860 C). The presence of Cu-Ti-based amorphous phase in the BZ, as shown earlier, signifies that the entire melt did not transform into crystalline phases upon solidification.…”
Section: B Phase Formation In the Braze Zonementioning
confidence: 99%
“…In Mg-(Ti + Cu) BM , in addition to Mg, Ti, Cu and Mg 2 Cu phases, low intensity peaks corresponding to Ti-Cu intermetallic phase can be seen; in contrast, in the un-ball milled, directly added Mg-Ti-Cu these peaks are not prominent. Considering that the formation enthalpies of various Ti-Cu intermetallics phases such as TiCu, TiCu 4 , TiCu 2 , Ti 2 Cu 3 , Ti 3 Cu 4 , Ti 2 Cu, Ti 3 Cu and TiCu 3 are close to each other, the reaction between Ti and Cu can result in any of these intermetallics phases [24][25][26][27][28]. On comparing the experimental diffraction peaks with the standard powder diffraction data, it can be associated to either Ti 2 Cu 3 or Ti 3 Cu phase.…”
Section: X-ray Diffractionmentioning
confidence: 99%
“…On comparing the experimental diffraction peaks with the standard powder diffraction data, it can be associated to either Ti 2 Cu 3 or Ti 3 Cu phase. However, as the Ti 2 Cu 3 intermetallic phase formation occurs only at ~780 °C to 860 °C and also at a much slower cooling rate, the observed Ti-Cu intermetallics peaks can hence be identified as Ti 3 Cu [25]. …”
Section: X-ray Diffractionmentioning
confidence: 99%